2015
DOI: 10.1111/2047-3095.12123
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for the Usefulness of Standardized Nursing Terminologies in Different Fields of Application: A Literature Review

Abstract: The use of standardized terminologies could be advantageous. However, there are shortcomings in nursing documentation and the use of standardized nursing terminologies that obstruct evaluation of nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
1
32
0
6
Order By: Relevance
“…Our results suggest SNTs are more widely implemented to code point-of-care nursing documentation in EHRs within clinical settings than previously thought. 74,75 The vast majority of studies conducted association analyses, employing methods such as multiple regression analysis, data clustering, and association mining techniques to select clinically important features and reduce dimensions of the dataset. Some also used decision trees, k-nearest neighbors, and support vector machines to identify hidden patterns in nursing data or to construct predictive models for patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest SNTs are more widely implemented to code point-of-care nursing documentation in EHRs within clinical settings than previously thought. 74,75 The vast majority of studies conducted association analyses, employing methods such as multiple regression analysis, data clustering, and association mining techniques to select clinically important features and reduce dimensions of the dataset. Some also used decision trees, k-nearest neighbors, and support vector machines to identify hidden patterns in nursing data or to construct predictive models for patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the availability of different standardized nursing terminologies and the incipient use of electronic records by nurses may contribute to the invisibility of some classification systems (Tastan et al, 2014). In European countries, for example, several rating systems are available for use, which is a limiting factor for the consensus, recommendation, and use of a single system (Törnvall & Jansson, 2017). Additionally, these limitations make it difficult to conduct multicenter studies in this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…This can be a risk when words can have different meanings, but in different contexts different degrees of precision are required to convey the concepts. An extensive review 25 showed that standardized nursing terminology was found to be essential for measuring, clarifying, and understanding nursing care. These same reasons apply for other professions to use standardized terminologies.…”
Section: Discussionmentioning
confidence: 99%